Measurement invariance of the Liebowitz Social Anxiety Scale‐Self‐Report. Issue 2 (9th July 2022) - Baroni, Duccio; Caccico, Laura; Ciandri, Serena; Di Gesto, Cristian; Di Leonardo, Laura; Fiesoli, Alice; Grassi, Elena; Lauretta, Francesco; Lebruto, Antonella; Marsigli, Nicola; Policardo, Giulia Rosa; Rosadoni, Martina; et al.
Abstract: Objective: The Liebowitz Social Anxiety Scale‐Self Report (LSAS‐SR) is a self‐report measure of social anxiety (SA), which has shown adequate psychometric properties across cultures. However, no study has systematically evaluated its measurement invariance (MI) between (a) individuals with and without a diagnosis of social anxiety disorder (SAD) and (b) males and females. The current study addresses this issue. Methods: We collected data on 257 (158 females) Italian individuals diagnosed with SAD and 356 (232 females) community‐dwelling adults. Results: We initially found support for the unidimensionality of the Italian LSAS‐SR measurement model in all samples. Using the Graded Response Model, we obtained evidence of partial MI and differential item functioning between community‐dwelling and SAD‐diagnosed individuals and evidence of strong MI between male and female participants. Conclusions: The results of this study suggest that the Italian LSAS‐SR measures the same trait in the same way across the symptom continuum and sexes, making it a psychometrically sound tool for assessment, screening, and research purposes.